Analysis of musculoskeletal injuries in elite female soccer players: Cohort study in one Brazilian team - Mariano, I. G. A.; Alves, L. E. M.; Rodrigues, E. K.; Azevedo, B. R.; Castro, A. L. O.; Mendonça, L. D. (Physical Therapy in Sport, 2025)
Abstract Purpose: The objectives of this study were to identify if preseason assessment variables predict lower limb musculoskeletal injuries in female soccer players and to compare characteristics between injured and non-injured athletes. Design: 4-month retrospective cohort study. Setting: An elite women's soccer team from Brazil. Participants: Twenty-seven female soccer players. Main outcomes measures: Lower limb length and asymmetry, hamstring flexibility, isokinetic strength of the hamstrings and quadriceps, single hop, lunge test, mSEBT, Thomas, trunk mobility, hip adductor strength, Bent-knee fall-out for testing hip range of motion, lateral trunk flexor endurance, Hip Sit, and single-leg and countermovement jump were recorded at baseline. Logistic regression analyses were performed to identify predictors for the occurrence of lower limb musculoskeletal injuries. Results: The logistic regression showed a significant model for lower limb musculoskeletal injuries. Trunk mobility, Hip Sit test, and were associated with injury (p = 0.016; R2 = 0,589). The model correctly classified 84.8% of cases (84.6% sensitivity and 85% specificity). The area under the receiver operating characteristic curve was 0.68 (95% CI: 0.53, 0.83; P < 0.024) demonstrating acceptable discriminative ability. Conclusion: The model showed that trunk mobility, Hip Sit, and Bent-knee fall-out were predictors of lower limb musculoskeletal injuries in female soccer players.